Penerapan LKPD Canva Berbasis Model PBL terhadap Kemampuan Berpikir Kritis Peserta Didik di Sekolah Dasar - Fajrin Hana Hamidah; Deviyanti Pangestu; Roy Kembar Habibi; Riswandi (Lentera: Jurnal Ilmiah Kependidikan, 2025)
The problem in this study is the application of LKPD canva based on the Problem Based Learning (PBL) model to critical thinking skills in the subject of science at SD Negeri 4 Tumijajar. The purpose of this study was to describe and analyze the effect of the application of LKPD canva based on the Problem Based Learning (PBL) model on the critical thinking skills of students in the subject of science in grade IV of SD Negeri 4 Tumijajar. The research method used is a quantitative method using a quasi-experiment. The population in this study were 45 students in grade IV of SD Negeri 4 Tumijajar, involving 45 students who were also used as research samples. Data collection techniques use test, observation and documentation techniques. The results of the data analysis show that there is an influence of the application of LKPD Canva based on the Problem Based Learning model on the critical thinking skills of the science subjects of grade IV students at SD Negeri 4 Tumijajar as indicated by the results of simple linear regression calculations with Fcount = 4.82 ≥ Ftable = 4.35 the percentage of completion of the experimental class is higher, namely 84%, which means it is at a strong level.